2017
DOI: 10.1007/s11120-017-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer and trapping in Synechococcus WH 7803

Abstract: Excitation energy transfer (EET) and trapping in Synechococcus WH 7803 whole cells and isolated photosystem I (PSI) complexes have been studied by time-resolved emission spectroscopy at room temperature (RT) and at 77 K. With the help of global and target analysis, the pathways of EET and the charge separation dynamics have been identified. Energy absorbed in the phycobilisome (PB) rods by the abundant phycoerythrin (PE) is funneled to phycocyanin (PC645) and from there to the core that contains allophycocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…The time-resolved fluorescence kinetics of intact Anabaena filaments share a lot of similarities with the reported kinetics from cells of different cyanobacterial strains (Mullineaux and Holzwarth 1991;Tian et al 2011;Acuña et al 2018b). Upon direct excitation of the PBS rods, the fluorescence kinetics in a few hundred picoseconds reflects primarily EET within the PBS, which is apparent by the similar DAES observed in cells and isolated PBS.…”
Section: Energy Transfer In Intact Cellssupporting
confidence: 60%
See 1 more Smart Citation
“…The time-resolved fluorescence kinetics of intact Anabaena filaments share a lot of similarities with the reported kinetics from cells of different cyanobacterial strains (Mullineaux and Holzwarth 1991;Tian et al 2011;Acuña et al 2018b). Upon direct excitation of the PBS rods, the fluorescence kinetics in a few hundred picoseconds reflects primarily EET within the PBS, which is apparent by the similar DAES observed in cells and isolated PBS.…”
Section: Energy Transfer In Intact Cellssupporting
confidence: 60%
“…An elaborated functional compartmental model of EET in Synechocystis PCC 6803 has been recently reported (van Stokkum et al 2018), according to which the slowest EET rates are between the core cylinders (115-145 ps) and between the rods and the core (68-115 ps). By time-resolved fluorescence, Acuña et al (2018b) reported a 20 ps EET time from the PBS terminal emitter to PSII, i.e. faster than the EET within the PBS.…”
Section: Introductionmentioning
confidence: 95%
“…The overall trapping of the excitation energy in PSI core occurs typically in 12-60 ps in cyanobacterial organisms and higher plants depending on the antenna size and the amount of red Chls (Croce et al 2000;Wientjes et al 2011;van Stokkum et al 2013;Akhtar et al 2018;Gobets et al 2001). The estimated PSI trapping observed in our model is ≈18 ps which is comparable with the previously observed lifetimes of ≈16 and ≈ 2 ps in Synechocystis and Synechococcus (Tian et al 2011;Acuna et al 2018a). The 18 ps PSI trapping seems to be a plausible average decay time considering the small amount of red Chl in a pool of ≈100 bulk Chls (cf.…”
Section: Target Analysissupporting
confidence: 88%
“…Megacomplex 1 involves PBS-PSII-PSI as PBS is well known to feed energy to both PSs, i.e. PBS coupled to both PSI and PSII (Liu et al 2013;Acuna et al 2018a;Tian et al 2011). PSII is known to be best described with a core which is in equilibrium with a non-radiative radical pair (RP) (Tian et al 2013).…”
Section: Target Analysismentioning
confidence: 99%
See 1 more Smart Citation